2020
DOI: 10.1080/00343404.2020.1808883
|View full text |Cite
|
Sign up to set email alerts
|

The role of technology and relatedness in regional trademark activity

Abstract: This paper provides insights on trademark activity at the regional level via two objectives. First, it examines the relationship between technological capabilities and new trademark applications. Second, it examines whether regions branch out to new trademark specializations that are related to their existing specializations. We employ EUIPO's data to study 218 European NUTS-2 regions (16 countries) over the period 2000-2016. Results show that increased technological stock is associated with more trademark app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…Our research also contributes to the nascent literature on the role of trademarks in industrial dynamics and regional innovation systems. In particular, we confirmed that trademarks may be complementary to patents as indicators of regional innovation capabilities and their evolution (as shown in this special issue by Block et al, 2021;Drivas, 2020;and Sáiz & Zofío, 2021). However, we show that regionally embedded knowledge protected by trademarks may only translate into higher entry rates in the absence of a pronounced appropriation strategy of incumbent firms or when entrants do not directly compete with the trademarking incumbents.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our research also contributes to the nascent literature on the role of trademarks in industrial dynamics and regional innovation systems. In particular, we confirmed that trademarks may be complementary to patents as indicators of regional innovation capabilities and their evolution (as shown in this special issue by Block et al, 2021;Drivas, 2020;and Sáiz & Zofío, 2021). However, we show that regionally embedded knowledge protected by trademarks may only translate into higher entry rates in the absence of a pronounced appropriation strategy of incumbent firms or when entrants do not directly compete with the trademarking incumbents.…”
Section: Discussionsupporting
confidence: 80%
“…Trademarks can aid the commercialization potential of firms' innovations and raise additional barriers to competing firms to imitate. Drivas (2020) finds that trademarks measure marketing and commercialization activities for exploitation of technological innovations. Crass (2014) shows that the use of brands is associated with a 35% increase in sales of innovative products and Arora et al (2016) finds that the use of trademarks helps incumbents prolong their technologybased first mover advantage on the market.…”
Section: Local Trademark Stocks and Knowledge Appropriationmentioning
confidence: 99%
“…This paper thus joins the formative work, not least in relation to Drivas (2020) as well as Sáiz and Zofío (2021) in this special issue, to demonstrate how trademark data might be adapted and used at the regional level. Our first aim is to help strengthen the bridge between the innovation studies literature that studies trademark filing behaviour, on the one hand, and the economic geography literature that emphasizes regional diversification, on the other.…”
Section: Introductionmentioning
confidence: 76%
“…Use of trademarks to trace product differentiation is in line with the product space approach (Hidalgo et al, 2007) that considers the relatedness of 'products' in the trade flows from countries (see also Capasso et al, 2019). Since trademarks and product-level trade flows are related, branching into new (or strengthening existing) trademarking activity provides a lens onto the regional comparative advantage (Drivas, 2020).…”
Section: Lesson For Our Approachmentioning
confidence: 99%
“…Further, given the relatively low standards and fees of obtaining trademarks, firmswith budget constraints may pursue trademark protection while relinquishing patent protection. [15] Copyright grants exclusive rights to the creators of original literary, scientific and artistic works. Copyright only prevents copying, not independent derivation.…”
mentioning
confidence: 99%